Місце внутрішнього операційного аудиту в системі внутрішньо-господарського контролю в організаціях різних форм власності - Бусарєв, В. В. (Ways to Improve Construction Efficiency, 2012)
The article, in fact, unite views of audit as a major form of internal controls for managing any economic entity (regardless of its ownership). As a result of this study was defined their own point of view on the possibility of organizing and conducting performance audit, revealing its considerable advantages for system management. Warning: the article focuses on the fundamental differences of internal business control of the performance audit and provides tips for improving functional processes control the enterprise regardless of ownership.